الصلاة في أوقات النهي: دراسة فقهية مقارنة - الجليل، البندري بنت عبدالله بن محمد (جامعة الأميرة نورة بنت عبد الرحمن, 2019)
فرض الله الصلوات الخمس وجعل لها أوقاتا محددة، وشرع التطوع بالصلاة أو النافلة في كل وقت للحاضر والمسافر، إلا أن هناك أوقاتا ورد النهى عن الصلاة فيها واجتمعت الأحاديث على ذكرها، وذكر الأسباب التي من أجلها نهي عن الصلاة فيها، هذه الأوقات هي موضوع البحث، (الصلاة في أوقات النهي)، وهي خمسة أوقات: وقت طلوع الشمس، ووقت غروبها، ووقت استوائها في وسط السماء، وبعد صلاة العصر، وبعد صلاة الصبح. وكان مما دفعني لكتابة هذا الموضوع أهميته، وحاجة كثير من الناس إلى معرفة أحكامه، حتى تقع تلك العبادة منهم على الطريقة المشروعة، وهو ما تهدف إليه هذه الدراسة من بيان أوقات النهي عن الصلاة، وتوضيح حكم الصلاة فيها، بطريقة بحثية معاصرة اتبعت فيها المنهج التحليلي المقارن. ومن أهم نتائج البحث: أن من تمام المحافظة على الصلاة والعناية بها حسن المحافظة على أدائها في أوقاتها، وأن الراجح في أوقات النهي عن الصلاة أنها خمسة: وقت طلوع الشمس، ووقت غروبها، ووقت استوائها في وسط السماء، وبعد صلاة العصر، وبعد صلاة الصبح. كما أن النهى عن الصلاة بعد العصر وبعد الصبح متعلق بفعل الصلاة، فلا يدخل وقت النهي بمجرد الزمان، ومن أهم أسباب النهي، مخالفة الكفار في وقت عبادتهم وترك التشبه بهم، وعدم مشروعية الصلوات التي لها سبب في أوقات النهي في الجملة؛ لأن النهي للتحريم والأمر للندب، وترك المحرم أولي من فعل المندوب، وجواز الصلاة على الجنازة بعد الصبح حتى تطلع الشمس، وبعد العصر حتى تميل للغروب، وكذلك جواز قضاء سنة الفجر بعد صلاة الفجر قبل طلوع الشمس، وكراهة الصلوات التي لا سبب لها في أوقات النهي. ومن أهم التوصيات: عمل مزيد من الأبحاث التي تهتم بدراسة مواقيت الصلاة والصيام، والتنبيه على حكم أداء العبادة فيها، سواء في البلاد الإسلامية أو في خارجها.
Allah has obligated the five prayers and established for them specific times. He has also recommended the nawafil or voluntary prayer throughout the day and night for he who is present as well as the traveller. But there are specific times that are considered forbidden according to various ahadeeth, and these ahadeeth also mention the reasons behind considering these hours forbidden. These times (prayer during the forbidden times) are the subject of this research and they are five: during sunrise, during sunset, when the sun is in the middle of the sky, after Asr prayer, and after the morning prayer. And what pushed me to write this topic is it's importance, and the need for people to know its ruling, so that they perform this aspect of worship in the correct manner. And this is the aim of this study; to clarify the forbidden hours and explain the ruling of praying during those hours, in a contemporary research that follows the analytical comparative approach. The most important results of this research are: maintaining and establishing prayers necessitates performing them during their established hours, and that the preferred opinion as to the forbidden hours is that they are five; during sunrise, during sunset, when the sun is in the middle of the sky, after Asr prayer, and after the morning prayer. Also, the prohibition of praying after Asr and after the morning prayer is related to the action of praying itself, so the forbidden hour is not only related to the specific time. Another important reason behind the forbidden hours is to oppose the disbelievers in their hours of worship and not imitate them. And the general impermissibility of praying (even with a reason) during the forbidden hours; as prohibition dictates impermissibility and orders dictate that an act is recommended, and leaving an impermissible act takes precedence over performing a recommended act. And the permissibility of praying on a funeral after the morning prayer until the sun has risen, and after Asr prayer until the sun sets. As well as the permissibility of making up the sunnah of fajr after the morning prayer before sunrise. And the disapproval of praying without a reason during the forbidden hours.
Keywords: مواقيت الصلاة -- العبادات الإسلامية -- الفقه الإسلامي